Diseño de la red eléctrica externa y la red hidráulica del Centro de Investigación de Energías Renovables y Eficiencia Energética de la Universidad Nacional de Loja. - Jumbo Ramírez, Holger Jesús (2012)
This thesis proposes the design external electrical and hydraulic design for the correct installation of fittings and pipes to supply water to the Research Center for Renewable Energy and Energy Efficiency, which is used for various research methods and techniques available today. As a slogan has been taken into account each of the variables present and that appear in the course design. With the design for the operation of these systems will be achieved somehow en sure proper construction and installation of both electrical and hydraulic net works to take advantage of these resources better, thanks to optimum performance.